PENGARUH FASE BULAN TERHADAP HASIL TANGKAPAN IKAN DI PELABUHAN MUNCAR KABUPATEN BANYUWANGI - Lestari, Nur Khamidah; Prihandono, Trapsilo; Nuraini, Lailatul (Universitas Jember, 2024)
The influence of the moon's phases in the sky is a factor that is closely related to the behavior of fish, one of which is the fish's attraction to light. The purpose of this research was to examine the differences in fish catches based on the phases of the moon at Muncar Port, Banyuwangi Regency. This type of research is descriptive quantitative research with ex post facto survey method. This research uses ex post facto research with a Causal Comparative Research design. The results showed that there was no difference in fish catch based on the phase of the moon in one year. The results of the analysis that has been carried out show that the average fish catch in each phase of the moon in one year is almost the same. Based on the research data, it can be concluded that in the bright moon, the fish catches are less. However, during the dark moon the fish catch becomes abundant.